Nitryl Chloride and Molecular Chlorine in the Coastal Marine Boundary Layer - Riedel, Theran P.; Bertram, Timothy H.; Crisp, Timia A.; Williams, Eric J.; Lerner, Brian M.; Vlasenko, Alexander; Li, Shao-Meng; Gilman, Jessica; de Gouw, Joost; Bon, Daniel M.; Wagner, Nicholas L.; Brown, Steven S; et al. (ENVIRONMENTAL SCIENCE & TECHNOLOGY, 2012)
The magnitude and sources of chlorine atoms in marine air remain highly uncertain but have potentially important consequences for air quality in polluted coastal regions. We made continuous measurements of ambient ClNO2 and Cl-2 concentrations from May 15 to June 8 aboard the Research Vessel Atlantis during the CalNex 2010 field study. In the Los Angeles region, ClNO2 was more ubiquitous than Cl-2 during most nights of the study period. ClNO2 and Cl-2 ranged from detection limits at midday to campaign maximum values at night reaching 2100 and 200 pptv, respectively. The maxima were observed in Santa Monica Bay when sampling the Los Angeles urban plume. Cl-2 at times appeared well correlated with ClNO2, but at other times, there was little to no correlation implying distinct and varying sources. Well-confined Cl-2 plumes were observed, largely independent of ClNO2, providing support for localized industrial emissions of reactive chlorine. Observations of ClNO2, Cl-2, and HCl are used to constrain a simple box model that predicts their relative importance as chlorine atom sources in the polluted marine boundary layer. In contrast to the emphasis in previous studies, ClNO2 and HCl are dominant primary chlorine atom sources for the Los Angeles basin.